Mathematical Study of One Prey and Two Competing Predators Considering Beddington-DeAngelis Functional Response with Distributed Delay - Gayathri P.; Babu, Raveendra (KOMUNITAS Analisis Matematika INDONESIA, 2023)
A nonlinear prey predator model is suggested and discussed to analyze the one prey and two competing predators considering Beddington-DeAngelis functional response with distributed delay. The analysis of stability of models is executed and the sufficient controls and suitable rules have been discussed for populations with the Beddington-DeAngelis functional response with distributed delay. All the feasible equilibria are observed and carried out for the stability rules. In the study, it has been observed that without delay at certain level of values the system would be stable. Additionally, we have supported our analytical conclusions with numerical visualisations.